CONSTRAINTS OF COMPLETE SYSTEMIC LAND REGISTRATION FISCAL YEAR 2020 ACCORDING TO REGULATIONS OF THE MINISTER OF AGRARIAN AND SPATIAL PLANNING/NATIONAL LAND AGENCY NUMBER 12 YEAR 2017 - Augyna Swietenia Prihadian; Ashinta Sekar Bidari; Hanita Mayasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Abstract : Implementation of the Complete Systematic Land Registration of the Karanganyar Regency Land Office in Sringin Village, Jumantono District, according to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency number 12 of 2017 can run well and smoothly in accordance with the Land Rights Certificate target of Sringin Village as many as 85 land parcels and Land Plane Map as many as 86 plots of land. Whereas in the implementation of the Complete Systematic Land Registration the Karanganyar Regency Land Office in Sringin Village, Jumantono District, there are obstacles, namely: Technical Constraints: factors that can hinder, hinder and limit the implementation of Complete Systematic Land Registration activities, namely in terms of cost, communication, time, HR, and the surrounding environment. Legal Constraints: factors that can hinder, hinder and limit legal issues including administrative constraints, oro - oro land problems and swap issues. Keywords: Oro-oro land, Complete Systematic Land Registration, ruilslag